PENERAPAN MEDIA PEMBELAJARAN CANVA DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XI DI SMA NEGERI 10 BULUKUMBA - Hidayat, Rahmat; Mustamin; Wahab, Abdul; Syahid, Akhmad; Raehana, Syarifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This thesis is entitled “The Implementation of Canva as a Learning Media to Increase Students’ Learning Motivation in Islamic Religious Education Subject for Grade XI at SMA Negeri 10 Bulukumba.” The main problems examined are: (1) How the implementation of Canva learning media can improve students’ learning motivation in Islamic Religious Education subject for Grade XI-8 at SMA Negeri 10 Bulukumba, and (2) Whether the implementation of Canva learning media can increase students’ learning motivation in Islamic Religious Education subject for Grade XI-8 at SMA Negeri 10 Bulukumba. To answer these questions, a classroom action research was conducted in the 2024/2025 academic year. This research employed Classroom Action Research (CAR) consisting of two cycles, each cycle comprising two meetings. Each cycle consisted of planning, implementation, observation, and reflection. The study was carried out in class XI-8 of SMA Negeri 10 Bulukumba with 32 students. Data were collected qualitatively through observation during the learning process and quantitatively through student questionnaires in each cycle. The data were analyzed qualitatively by describing the results of each action during the learning process, and quantitatively using descriptive statistics such as mean scores and percentages. The results showed that students’ learning motivation increased. The quality of learning was marked by the improvement of students’ motivation and activeness in the classroom, as observed during the research process. Questionnaire results indicated that students’ learning motivation improved from the pre-cycle (65.93), to cycle I (73.62), and further to cycle II (90). Thus, students’ learning motivation significantly increased through the use of Canva as a learning media.